What can hornworts teach us? - Frangedakis, Eftychios; Marron, Alan O.; Waller, Manuel; Neubauer, Anna; Tse, Sze Wai; Yue, Yuling; Ruaud, Stephanie; Waser, Lucas; Sakakibara, Keiko; Szövényi, Péter (Frontiers in Plant Science, 2023)
The hornworts are a small group of land plants, consisting of only 11 families and approximately 220 species. Despite their small size as a group, their phylogenetic position and unique biology are of great importance. Hornworts, together with mosses and liverworts, form the monophyletic group of bryophytes that is sister to all other land plants (Tracheophytes). It is only recently that hornworts became amenable to experimental investigation with the establishment of Anthoceros agrestis as a model system. In this perspective, we summarize the recent advances in the development of A. agrestis as an experimental system and compare it with other plant model systems. We also discuss how A. agrestis can help to further research in comparative developmental studies across land plants and to solve key questions of plant biology associated with the colonization of the terrestrial environment. Finally, we explore the significance of A. agrestis in crop improvement and synthetic biology applications in general.